Methodology for a correlate of protection for group B Streptococcus: Report from the Bill & Melinda Gates Foundation workshop held on 10 and 11 February 2021. Issue 32 (30th July 2022) - Gilbert, Peter B.; Isbrucker, Richard; Andrews, Nick; Goldblatt, David; Heath, Paul T.; Izu, Alane; Madhi, Shabir A.; Moulton, Lawrence; Schrag, Stephanie J.; Shang, Nong; Siber, George; Sobanjo-ter Meulen, Ajoke
Abstract: Worldwide, childhood mortality has declined significantly, with improvements in hygiene and vaccinations against common childhood illnesses, yet newborn mortality remains high. Group B Streptococcus (GBS) disease significantly contributes to newborn mortality and is the leading cause of meningitis in infants. Many years of research have demonstrated the potential for maternal vaccination against GBS to confer protection to the infant, and at least three vaccine candidates are currently undergoing clinical trials. Given the relatively low disease incidence, any clinical vaccine efficacy study would need to include at least 40, 000 to 60, 000 participants. Therefore, a path to vaccine licensure based on a correlate of protection (CoP) would be the preferred route, with post-approval effectiveness studies demonstrating vaccine impact on reduction of disease burden likely to be required as part of conditional marketing approval. This workshop, hosted by the Bill & Melinda Gates Foundation on 10 and 11 February 2021, discussed considerations and potential statistical methodologies for establishing a CoP for GBS disease. Consensus was reached that an antibody marker with global threshold predictive of a high level of vaccine protection would be most beneficial for licensure assessments. IgG binding antibody in cord blood would likely serve as the CoP, with additional studies needed to confirm a high correlation with functional antibody and to demonstrate comparable kinetics of natural versus vaccine-induced antibody. Common analyses of ongoing seroepidemiological studies include estimation of absolute and relative disease risk as a function of infant antibody concentration, with adjustment for confounders of the impact of antibody concentration on infant GBS disease including gestational age and maternal age. Estimation of an antibody concentration threshold indicative of high protection should build in margin for uncertainties from sources including unmeasured confounders, imperfect causal mediation, and variability in point and confidence interval estimates across regions and/or serotypes.